(untitled) (KULT_online, 2009)
Using a thoroughly interdisciplinary approach, Miriam Y. Arani plumbs little-researched sources and examines the photographies of Poles and Germans during the period of German occupation from 1939-1945. Using the example of Reichsgau Wartheland, Arani delivers a history of visual identity constructs that is also a comprehensive photographic record of the occupation period. The results are fascinating, but would have been shown to better advantage if the volume’s 1000-plus pages had been subject to some judicial edits.